Beautiful Federal Building at night (Curt Teich & Co., Inc.)
The three fluted towers represent the three branches of our Federal Government, Executive, Judicial, and Legislative. The sides of the triangles are the Halls of Thirty States, whose flags and shields join with the unusual coloring of the building itself, and makes the interior court an outstanding accomplishment in modern architecture.